Teaching-Leaning French by Using Mind Mapping Technique for Students Grade 4 at Demonstrated Secondary School, Luang Prabang Teacher Training College, Academic Year 2022-2023 - HATSADY, Soudachanh; PHENGBOUNPHET, Thidaphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Based on observations of current teaching and learning practices, it was found that many students are still unable to read and write independently. Their proficiency in French, particularly in language development and vocabulary retention, remains limited. This weakness is reflected in students’ academic performance, as approximately 70% of learners across different classes achieved low to average scores. Although several factors may contribute to students’ limited academic achievement, the consistent application of effective pedagogical approaches plays a crucial role in supporting systematic knowledge acquisition and the practical application of learned content. Therefore, improving learning outcomes requires teachers to integrate innovative instructional strategies alongside existing teaching methods to enhance the overall quality of instruction. The objectives of this research were threefold: (1) to examine the effectiveness of teaching and learning French using the Mind Mapping method for Grade 4 students at Sathid Secondary School based on the 80/80 efficiency criterion, (2) to study the effectiveness of students’ learning outcomes achieved through the Mind Mapping teaching method, and (3) to investigate students’ satisfaction with the use of Mind Mapping in French instruction. The research sample consisted of 24 Grade 4 students selected through purposive sampling. Research instruments included five French lesson plans, achievement tests comprising 50 items derived from the lesson plans, and a student satisfaction questionnaire with 20 items using a five-level rating scale. Data were analyzed using Microsoft Excel to calculate the mean (X̄) and standard deviation (SD). The results revealed that: (1) the effectiveness of French instruction using the Mind Mapping method was 88.00/90.58, exceeding the established 80/80 criterion; (2) students’ learning outcomes demonstrated an effectiveness index of 0.81; and (3) students reported the highest level of satisfaction with French learning activities implemented through the Mind Mapping teaching method.